Baelo-Allué, S. and Calvo-Pascual, M. (Eds.) (2021). Transhumanism and posthumanism in twenty-first century narrative. Routledge. 236 pp. ISBN 78-0-367-65513-6 - Biano, Ilaria (Journal of Posthumanism, 2023)
The basic tenet through which Sonia Baelo-AlluÃ© and MÃ³nica Calvo-Pascual frame their edited collection is the conviction that the world emerged from four consecutive and relatively quick industrial revolutions have been profoundly shaped by the technological development, and exponential growth determined by that processes. And the way that shaping has acted on culture, society, and people can be â€“ and has been â€“ understood both â€œas marks of progress or as processes of dehumanizationâ€ depending on how we conceive â€œprogress and being humanâ€ (p. 1). The perspective we adopt to read the world and its processes determines the valuation of those processes. As basic and obvious as this consideration may seem, it actually has a lot of value when touching the subjects this edited collection aims at analyzing through contemporary fiction.